Factors That Influence Brand Loyalty In Skintific Consumers - Candani, Ayu Meiratara Karunika Meta; Yuniardi Rusdianto, (Jurnal Manajemen, 2023)
Currently, the development of the beauty industry has a very rapid growth with very high competition. Proven by the emergence of various brands of beauty products on offer, ranging from products for facial skin, lips to whole body care. the purpose of the study was to determine the brand image, brand trust, and perceived quality simultaneously significant effect on brand loyalty in skintific products. This study uses descriptive and associative approach methods as the basis for the form of research, the population in this study were female teenagers in Surabaya City, namely 117,814 people with a sample size of 100 female teenagers in Surabaya City who used Skintific products. The results of this study are that the Brand Image variable (X1) has no partial effect on Brand Loyalty (Y), the Brand Trust variable (X2) has a partial effect on Brand Loyalty (Y), the Perceived Quality variable (X3) has a partial effect on Brand Loyalty (Y).